Charles Mason Remey family papers - Remey, Charles Mason, 1874-1974.; Mason, Charles, 1804-1882.; Remey, George Collier, 1841-1928.; Remey, Mary Josephine Mason, 1845-1938.
Correspondence, diaries, journals, genealogical papers, photographs, and other papers of Remey and Mason family members. Primarily the papers of Charles Mason Remey relating to his activities on behalf of the Bahai Faith. Also includes papers of George Collier Remey pertaining to his service with the U.S. Navy during the Civil War, the Spanish-American War, the Philippine American War, and the Boxer Rebellion; papers of Iowa jurist and temperance and women's rights advocate, Charles Mason; and papers of Mary Josephine Mason Remey.
Charles Mason Remey, architect, and other Remey (Ramey) and Mason family members.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Mason family; Ramey family; United States. -- Navy; Bahai Faith; Courts -- Iowa; Spanish-American War, 1898.; Temperance; Women's rights; China -- History -- Boxer Rebellion, 1899-1901.; Philippines -- History -- Philippine American War, 1899-1902.; United States -- History -- Civil War, 1861-1865.; Architects